Rituals and Embodied Cultural Practices at the Beginning of Life: African Perspectives - Magdalena Ohaja (MDPI AG, 2021)
Cultural beliefs and practices find expression through rituals. Rites of initiation or passage are some of the most common rituals among the indigenous African societies. Pregnancy and Childbirth are not only biological events, but also socially and culturally constructed with associated symbols that represent the social identities and cultural values of Africans. Birth is a rite of passage, and children are perceived as special gifts from the Supreme Being. As such, pregnancy and childbirth are special events cherished and celebrated through varied rituals. Drawing on empirical literature and relevant commentaries, this paper aims to discuss selected rituals and embodied practices surrounding the start of life (pregnancy, birth, and early motherhood). The paper will specifically focus on the following aspects: pregnancy rituals; birth songs and dancing; the omugwo (care after birth); the cord and placenta rituals; and the naming ceremony. Some of the pregnancy rituals are purificatory in nature and therefore beneficial for maternal and infant health. The celebrations surrounding the birth of a child are community events, marked with singing and dancing. Following childbirth, the new mothers are not expected to participate in house chores to allow them time to recuperate. In all, discourses concerning the beginning of life, i.e., pregnancy and the periods surrounding it, are filled with rituals which are embodiments or expressions of cultural values, customs, and beliefs.